Literacy Character Education Planning to Strengthen the Pancasila Student Profile through Local Culture in Early Childhood Education - Suratmi, Suratmi; Hartono, Hartono; Diana (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2024)
This study explores the planning of character education projects to strengthen the Pancasila student profile through local culture in early childhood education at TK Sukoharjo 1 and TK Desa Majasto 02. Employing a descriptive qualitative case study approach, data were gathered through interviews, observations, and document studies. The findings reveal comprehensive strategies for planning, implementing, and evaluating character education projects. At TK Sukoharjo 01, the project involved forming a facilitator team, identifying readiness stages, and developing specific learning modules. Implementation utilized real-life experiences such as gardening and local markets, while evaluation focused on cooperation, communication, and care. At TK Desa Majasto 02, the project preparation included curriculum development, facilitator team formation, and methods centered around the local culture of "Ngapem," emphasizing global diversity, cooperation, and independence. The implications of these findings are profound for educational policy and practice. Integrating local cultural practices into character education effectively strengthens the Pancasila student profile, fostering values essential for national cohesion and global citizenship. These insights suggest that policymakers and educators should adopt similar culturally embedded educational frameworks, ensuring that character education is theoretically sound, practically relevant, and contextually appropriate. Despite the promising outcomes, limitations include the study's scope confined to two early childhood centers and reliance on qualitative data. Future research should explore applying similar projects in diverse settings, investigating long-term impacts, and integrating quantitative measures to enhance the evidence base.